2001
DOI: 10.1081/jdi-100001294
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxic Periodic Paralysis in a Patient Abusing Thyroxine for Weight Reduction

Abstract: Thyrotoxic periodic paralysis is a rare endocrine disorder most prevalent among individuals of Asian descent that presents as proximal muscle weakness, hypokalemia, and signs of hyperthyroidism. We present an unusual patient with previous normal thyroid function who had abused thyroxine as antiobesity pills and developed periodic paralysis affecting the upper and lower limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 5 publications
0
26
0
2
Order By: Relevance
“…Hyperthyroidism is associated with weight loss through an increased metabolic rate. Exogenous thyroid hormone use has been associated with episodes of thyroid storm as well as thyrotoxic periodic paralysis [66,67]. Thyrotoxic periodic paralysis is an acute complication of thyrotoxicosis and often seen in those of Asian descent [68].…”
Section: Thyroid Hormonementioning
confidence: 99%
“…Hyperthyroidism is associated with weight loss through an increased metabolic rate. Exogenous thyroid hormone use has been associated with episodes of thyroid storm as well as thyrotoxic periodic paralysis [66,67]. Thyrotoxic periodic paralysis is an acute complication of thyrotoxicosis and often seen in those of Asian descent [68].…”
Section: Thyroid Hormonementioning
confidence: 99%
“…As freqüências foram maiores entre as mulheres mais jovens e obesas e de nível sócio-econômico mais elevado (valor de p < 0,001). Os níveis de TSH foram estatisticamente menores entre as usuárias de fórmulas (1,96 mUI/ml; IC 95% = 1,93-1,98) comparados com usuárias prévias 2,83 mUI/ml (IC 95% = 2,13-3,02) e não usuárias 2,59 mUI/ml (IC 95% = 2,20-3,21 (1)(2)(3). A study in two Brazilian metropolitan cities have also shown that four to six active components predominated in these prescriptions, but there were prescriptions listing as many as 17 components.…”
Section: Níveis De Tsh Associados Ao Uso De Fórmulas Para Emagrecer Eunclassified
“…The most common cause of TPP in thyrotoxicosis is Graves' disease, although TPP can occur with any form of thyrotoxicosis (1, 2). It is less commonly associated with thyroiditis (3, 4), toxic adenoma (5), T4 ingestion and iodine excess (6). However, very few cases such as this one have been reported as far as we know that thyrotoxic periodic paralysis associated with painless thyroiditis.…”
Section: Introductionmentioning
confidence: 99%